The Effects of Globalization on Social Development of Franc Zones Countries - Franklin, Dongmo Tsobjio; Ibrahim, Ngouhouo Nji; Benjamin, Fomba Kamga (Asian Journal of Economic Modelling, 2020)
This work aims to bring out the effects of economic and financial globalization on the unemployment rate evolution in the franc zone. We started to bring out the effects of globalization at the level of all the Franc Zone countries before making a comparative analysis between the CEMAC and the UEMOA zone. After having chosen the simple model at the end of the statistical tests for the regression at the level of all the countries of the Franc Zone, the results obtained showed that foreign direct investments (FDI) influence negatively and significantly the rate unemployment; just as the price index negatively influences the unemployment rate. These results indicate that FDI contributes to lower the unemployment rate in all the countries of the franc zone. As for other variables, they have positive effects and contribute to increasing the unemployment rate in the Franc Zone. Then, the results obtained from the comparative analysis between the CEMAC and the UEMOA Zone from the regression of a naive model, made it possible to note the diverging and converging effects between these two zones taken each separately on one hand and by comparing them to the results obtained at the global level on the other hand. In general, monetary, debt, trade and investment policies must be restructured in order to make them socially beneficial in the Franc Zone because in their current state, they seem to hinder the social development of this area.